2007
DOI: 10.1113/expphysiol.2006/036889
|View full text |Cite
|
Sign up to set email alerts
|

A novel role for P450 eicosanoids in the neurogenic control of cerebral blood flow in the rat

Abstract: The P450 eicosanoids epoxyeicosatrienoic acids (EETs) are endogenous lipid mediators produced in the brain by P450 epoxygenases and metabolized through multiple pathways, including soluble epoxide hydrolase (sEH). Epoxyeicosatrienoic acids play important functions in the brain, including regulation of cerebral blood flow and protection from ischaemic brain injury. We previously demonstrated that ischaemic preconditioning induces cytochrome P450 2C11 epoxygenase (CYP2C11) expression in the brain, and that pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 22 publications
1
38
0
Order By: Relevance
“…There is also evidence that specific CYP2C forms are expressed in the rodent brain, including the cortex and hippocampus (Alkayed et al, 1996;Luo et al, 1998;Riedl et al, 2000;Iliff et al, 2007). CYP2C11 expressed in astrocytes and perivascular neurons was proposed to be an arachidonic acid epoxygenase involved in the regulation of cerebral blood flow in rats (Alkayed et al, 1996;Iliff et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is also evidence that specific CYP2C forms are expressed in the rodent brain, including the cortex and hippocampus (Alkayed et al, 1996;Luo et al, 1998;Riedl et al, 2000;Iliff et al, 2007). CYP2C11 expressed in astrocytes and perivascular neurons was proposed to be an arachidonic acid epoxygenase involved in the regulation of cerebral blood flow in rats (Alkayed et al, 1996;Iliff et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…CYP2C11 expressed in astrocytes and perivascular neurons was proposed to be an arachidonic acid epoxygenase involved in the regulation of cerebral blood flow in rats (Alkayed et al, 1996;Iliff et al, 2007). Human CYP2C family enzymes may play a similar role in regulating cerebral blood flow (Gervasini et al, 2004); CYP2C8 and CYP2C9 were shown to have arachidonic acid epoxygenase activity (Rifkind et al, 1995) and CYP2C9 has been suggested to regulate blood flow in skeletal muscle during exercise (Hillig et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were present in both SR and SS and highly significant in all subjects together. Previously reported relationships between epoxyeicosatrienoic acids and the autonomic nervous system include (1) arachidonic acid mediated by endogenous 5,6-EET, which can be blocked by CYP450 inhibitors and restored by exogenous 5, ; (2) coexpression of epoxygenases and sEH in brain parasympathetic perivascular nerves 21 ; and (3) production of EETs by sympathetic superior cervical ganglia neurons in culture. 22 Mechanisms for these interactions have not been elucidated, and there is no evidence for either catecholamine stimulation of epoxygenases or for EET-induced norepinephrine release from sympathetic terminals in whole animals or humans.…”
Section: Discussionmentioning
confidence: 99%
“…The CYP2C8 rs17110453 polymorphism may decrease the activity of CYP2C8, thereby decreasing the levels of circulating EET metabolites. Pharmacological inhibition or genetic deletion of sEH (encoded by the EPHX2 gene) has been shown to increase EET levels and protect against stroke-induced brain injury 49,50) . Furthermore, certain gene polymorphisms of human EPHX2 have been shown to increase sEH activity and thereby increase the incidence of IS 21) .…”
Section: Logistic Regression Analysismentioning
confidence: 99%